Computed tomography brain scan findings in eclampsia - Madhavi, K. N.; Karuna, Guguloth; Sivaranjani, B. S. V.; Sreevalli, Mokana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Eclampsia is characterized by sudden onset of generalized tonic-clonic convulsion or coma in pregnancy or postpartum unrelated to other cerebral conditions. It is a life-threatening complication of pregnancy; the exact cause is still not conclusively elucidated. Recent studies using computed tomography and magnetic resonance imaging (MRI) gives valuable neuroimaging findings to determine the prognosis and early management of neurovascular complications that will reduce maternal mortality and morbidity. Methods: This is a prospective study done over 6 months to study population was chosen by eclampsia patients who were admitted through the emergency ward and also indoor patients who developed eclampsia after admission. A total of 50 patients were analyzed. Computed tomography (CT) scan of brain performed after a confinement of fetus and after stabilizing the mother. Maternal and fetal outcomes were observed in these cases. Results: A total of 50 eclampsia patients and their CT scan findings were studied. In these positive CT scan findings were noticed in 23 patients. 1 patient expired with massive cerebral hemorrhage and cerebral oedema (40%) was the most common CT scan finding and the most common area is the parietal lobe (32%) followed by the occipital (8%) and frontal 4% and all lobes (1%). Conclusions: CT scan findings provide valuable information about the neurovascular complication in eclampsia patients, early diagnosis and prompt management of these complications will reduce maternal and perinatal mortality to some extent.